Aku mengenal diriku: Peningkatan kesadaran diri anak usia 5–6 tahun melalui metode bernyanyi di TK Bakti Terpadu - Puji Lestari; Hanita Hanita; Reni Ardiana; Nazmi Soraya (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2026)
Self-awareness is one of the basic competencies in early childhood social-emotional development that plays an important role in the ability to recognize emotions, control behavior, and build positive social interactions. The results of the pre-cycle at Bakti Terpadu Kindergarten show that most children aged 5-6 years still have difficulty recognizing feelings, following directions, and showing confidence during the learning process. This research aims to increase children's self-awareness through the application of the singing method. The research uses the Classroom Action Research (PTK) approach with the Kemmis and McTaggart models which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 11 children aged 5-6 years at the Integrated Bakti Kindergarten. Data was collected through observation and documentation, then analyzed using quantitative descriptive techniques in the form of percentages. The results of the study show that the application of the singing method is able to increase children's self-awareness gradually. The achievement percentage increased from 27.3% in the pre-cycle stage to 45.05% in Cycle I and reached 100% in Cycle II, thus exceeding the set success indicators. This improvement is shown through the development of children's ability to recognize and manage emotions, follow teachers' directions, adjust to the learning environment, build positive interactions, and increase confidence.